2006
DOI: 10.1111/j.1463-1318.2005.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Stapled haemorrhoidopexy in fourth degree haemorrhoidal prolapse: is it worthwhile?

Abstract: Third degree haemorrhoidal prolapse remains the best indication for stapled haemorrhoidopexy. This procedure may also be indicated in fourth degree haemorrhoidal prolapse. Patients with fourth degree haemorrhoids may be subjected to this procedure following adequate discussion of the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 28 publications
1
36
1
1
Order By: Relevance
“…53 It is thought that this is secondary to the irreducibility of the prolapse precluding the lifting effect of the stapled hemorrhoidopexy. 32,57 Technical characteristics of the procedure have also been shown to be implicated in the development of recurrent hemorrhoids, including the placement of the purse string, the level of the staple line, and the completeness of the mucosectomy ring. 53 It was identified that patients who have recurrence following stapled hemorrhoidopexy were more likely to undergo re-interventional treatments, such as excisional hemorrhoidectomies, than patients who have initially undergone other methods of hemorrhoidectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 It is thought that this is secondary to the irreducibility of the prolapse precluding the lifting effect of the stapled hemorrhoidopexy. 32,57 Technical characteristics of the procedure have also been shown to be implicated in the development of recurrent hemorrhoids, including the placement of the purse string, the level of the staple line, and the completeness of the mucosectomy ring. 53 It was identified that patients who have recurrence following stapled hemorrhoidopexy were more likely to undergo re-interventional treatments, such as excisional hemorrhoidectomies, than patients who have initially undergone other methods of hemorrhoidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…5,54,55 The judicious careful use of an Eisenhammer retractor for purse string suture insertion has been shown to reduce the incidence of these complications. 56,57 Soiling and mucus discharge was also documented. 4,9,30,32,46 Fecal urgency was also noted with an incidence range of 0.2 to 25% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors, recurrent rectal prolapse was significantly more frequent in patients with fourth-degree hemorrhoids, so that they may not represent an appropriate indication for stapled hemorrhoidopexy [49,50,76]. Actually, in patients with only third-degree hemorrhoids, recurrence is similar in both stapled hemorrhoidopexy and conventional hemorrhoidectomy [77].…”
Section: Resultsmentioning
confidence: 99%
“…In the existing literature, this complication occurs in 4 to 25 % of cases [41][42][43][44][45][46][47][48]. Bleeding predominantly affects patients with fourth-degree hemorrhoids [49,50]. Most bleeding complications occur during operation at the staple line and should be managed with suture of the bleeding points, after a careful inspection of the stapled suture line [49,50].…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation